Prevalence of Hemoglobinopathies in Patients of Ischemic Stroke - Irfan, Fariha; Tahir, Asad; Mazhar, Kanwal (Biological and Clinical Sciences Research Journal, 2025)
Hemoglobinopathies are known contributors to cerebrovascular complications, yet their role in ischemic stroke remains underexplored in many populations. Objective: To determine the prevalence of hemoglobinopathies among patients diagnosed with ischemic stroke and examine their association with demographic and clinical variables. Methods: This cross-sectional study was conducted over six months at the Department of Neurology, Fauji Foundation Hospital, Rawalpindi from April 2024 to August 2024. A total of 374 patients aged 30–70 years with confirmed ischemic stroke were enrolled using non-probability consecutive sampling. Patients with prior diagnoses of hemoglobinopathy, recent blood transfusions, or comorbid conditions such as chronic kidney disease were excluded. Blood samples were collected and analyzed using PCR for hemoglobinopathy genotyping. Results: Out of 374 patients, 320 (85.6%) had AA genotype, 38 (10.2%) had sickle cell trait (AS), and 16 (4.3%) had homozygous CC genotype. A statistically significant association was observed between gender and hemoglobinopathy status (p = 0.032), with homozygous CC more common in males. Clinical features such as seizures and coma were more frequent among patients with hemoglobinopathy. No significant associations were found with age group, weight, or residential status. Conclusion: It is concluded that hemoglobinopathies, especially sickle cell trait and homozygous CC, are present in a significant proportion of ischemic stroke patients. These findings support the inclusion of hemoglobinopathy screening in stroke evaluation protocols, particularly in genetically at-risk populations.